ALIGNMENT POROS POMPA BENFIELD 1107-JB MENGGUNAKAN DIAL INDIKATOR DENGAN METODE RIM AND FACE - Afif Chaniago Bastiar; Yovan Witanto; Dedi Suryadi (UNIB Press, 2023)
Alignment is a process that aligns two shaft axes that are not straight to centric (between the driving shaft and the driven shaft axis). Correct alignment is needed so that the clutch run out check is correct, so that parallel misalignment and angular misalignment do not occur which caused the industry to lose billions of dollars. The purpose of this research is to analyze the alignment performance on the Benfield 1107 JB PT pump shaft. PUSRI to create the correct alignment. The method used in this study is a dial indicator with the face and rim method. The measuring instrument used is a Dial Indicator with a detailed accuracy of 0.01 mm with radial and axial measurements. The results show a different final value for each angle used. From the difference in values ​​obtained, namely in the radial direction the angle is 0o which is 0 mm, the 90o angle is 0.07 mm, the 180o angle is 0.14 mm, and the 270o angle is 0.07 mm, and the difference in value in the axial direction is the angle 0o is 0 mm, 90o angle of 0.01 mm, 180o angle of 0.01 mm, and 270o angle of 0 mm indicates that the 1107-JB Benfield Pump is ready to operate again on the P-IV Ammonia section.